Phylogenomic analysis of the Neotropical fish subfamily Characinae using ultraconserved elements (Teleostei: Characidae) - Souza, Camila S. [UNESP] (2022)
Characinae is one of the most species-rich subfamilies of Characidae and holds special taxonomic importance because it includes Charax, type-genus of Characidae and Characiformes. Currently, the monophyly and the hypotheses of intergeneric and interspecific relationships of Characinae are based on a few morphological and molecular studies but all with low species coverage. Given their diversity, taxonomic importance, and the lack of a taxon-dense phylogeny, we sought to buttress the systematic understanding of Characinae collecting DNA sequence data from ultraconserved elements (UCEs) of the genome from 98 specimens covering 57 species (61%) plus 17 characiforms as outgroups. We used maximum likelihood, Bayesian inference, and coalescent-based species tree approaches and the resulting phylogeny with 1,300 UCE loci (586,785 characters) reinforced the monophyly of the subfamily as well as of six genera: Acestrocephalus, Charax, Cynopotamus, Galeocharax, Phenacogaster, and Roeboides. The phylogeny provides a hypothesis of intergeneric and interspecific relationships for the subfamily with Phenacogaster sister to all genera, and Acanthocharax sister to Cynopotamini (Cynopotamus (Acestrocephalus Galeocharax)) and Characini (Charax Roeboides). We propose a new tribe Acanthocharacini to allocate Acanthocharax, two subclades for Phenacogaster, two for Cynopotamus, three for Charax, and reinforced the four subclades for Roeboides previously identified by morphological studies. Additionally, we generated a time-calibrated phylogeny for Characinae that suggested an initial diversification during the Miocene at around 19 million years ago and discussed historical biogeographic events for major subclades. The results obtained here will contribute to the development of further research on the evolutionary processes modulating species diversification in Characinae.